First-Principles Study on Adsorption and Decomposition of NOx on Mo (110) Surface - Yunmi Huang; Haijun Luo; Changkun Dong (Advances in Condensed Matter Physics)
Based on the density functional theory, the adsorption and decomposition of NOx (x = 1, 2) on Mo (110) surface are studied with first-principles calculations. Results show that the stable structures of NO2/Mo (110) are MoNO2 (T, μ1-N), MoNO2 (H, μ3-N, O, O′), MoNO2 (S, η2-O, O′), and MoNO2 (L, η2-O, O′). The corresponding adsorption energies for the structures are −3.83 eV, −3.40 eV, −2.81 eV, and −2.60 eV, respectively. Besides, the stable structures of NO/Mo (110) are MoNO (H, μ1-N), MoNO (H, μ2-N, O), and MoNO (H, η1-N) with the corresponding adsorption energies of −3.75 eV, −3.57 eV, and −3.01 eV, respectively. N and O atoms are easily adsorbed at the hollow sites on Mo (110) surfaces, and their adsorption energies reach −7.02 eV and −7.70 eV, respectively. The preferable decomposition process of MoNO2 (H, μ3-N, O, O′) shows that the first and second deoxidation processes need to overcome energy barriers of 0.11 eV and 0.64 eV, respectively. All these findings indicate that NO2 is relatively easy to dissociate on Mo (110) surface.